THE IMPACT OF CLIMATE CHANGE ON HUMAN HEALTH: DOES LEGISLATION IN SERBIA ADEQUATELY RESPOND TO THE CHALLENGES? - Nikolić Popadić, Sofija (Pravni zapisi, 2025)
The effects of climate change are numerous: from extreme weather events with enormous amount of precipitation, to extreme droughts in parts of the planet where this was previously uncommon. They can significantly affect the physical and mental health of the human population. This paper will focus firstly on recognizing the increasingly intense consequences of climate change in Serbia and their impact on human health. After that, it will answer the question whether the threat of climate change to human health is recognized in the strategies and legal regulations in Serbia, and if so, whether legislation in Serbia adequately responds to those challenges. The research results show that the connection between the climate change and human health is not recognized in all relevant legislation. Recommendations for appropriate legislative changes are provided.
Keywords: Climate Change; Human Health; Health Law; Climate Change Law; Strategies